Efficient Photolytic Breakdown of Waste Polystyrene Foam Using an “All-in-One” Photo-HAT Reagent at Ambient Conditions - Cakir, Yusra Bahar; Uzun, Ragip Talha; Kiliclar, Huseyin Cem; Kaya, Kerem; Jockusch, Steffen; Yagci, Yusuf; Kiskan, Baris (ACS sustainable chemistry & engineering, 2024)
Upcycling/recycling of waste polymers to reduce the exponentially increasing plastic pollution is an environmental subject of great importance. Accordingly, in this work, we propose the use of an “all-in-one” photolytic hydrogen atom transfer (photo-HAT) reagent (phenacyl bromide) that can in situ generate bromine radicals, acetophenone, HBr, and H2O2, resulting in a total of four well-established, potent intermediates for the photodegradation/photodepolymerization of waste polystyrene (PS) foam. Under ambient conditions, using ethyl acetate solvent and the stated photo-HAT catalyst, waste PS (M n > 120 kg/mol) breaks down to oligomers with less than eight styrene units (M n < 0.76 kg/mol) and to several organic compounds, such as aromatic ketones, oxygenated alkenes in conjunction with acetophenone and trace benzoic acid. A plausible reaction mechanism demonstrating the role of each in situ generated intermediate involved in this photodegradation is proposed. Herein, we present an efficient metal-free photo-oxidative degradation method for commercial PS using a cheap organic reagent at ambient sustainable conditions. Ultimately, this study provides a promising alternative to recent waste polymer valorization methods involving toxic transition metal salts and halogenated solvents.